2013
DOI: 10.3322/caac.21184
|View full text |Cite
|
Sign up to set email alerts
|

Understanding, recognizing, and managing toxicities of targeted anticancer therapies

Abstract: Answer questions and earn CME/CNE Advances in genomics and molecular biology have identified aberrant proteins in cancer cells that are attractive targets for cancer therapy. Because these proteins are overexpressed or dysregulated in cancer cells compared with normal cells, it was assumed that their inhibitors will be narrowly targeted and relatively nontoxic. However, this hope has not been achieved. Current targeted agents exhibit the same frequency and severity of toxicities as traditional cytotoxic agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
205
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(223 citation statements)
references
References 243 publications
(279 reference statements)
2
205
0
9
Order By: Relevance
“…Ironically, given its broad spectrum of activity in the absence of systemic side effects, RRx-001 is more highly targeted than, for example, the kinase inhibitors, which carry a label of 'precision medicine' and are referred to as 'targeted', but because binding can occur in all tissues of the body, can result in off-target (nontumor specific) toxicities that affect virtually every organ system in the body [34]. The ironic legacy of the molecularly targeted agents is that they are no less toxic or more 'precise' than the standard chemotherapy they were designed to replace, and while targeted therapies with broad activity, such as multikinase inhibitors, possess both activity and toxicity in equal measure, highly selective kinase inhibitors often have activity tuned out.…”
Section: Discussionmentioning
confidence: 99%
“…Ironically, given its broad spectrum of activity in the absence of systemic side effects, RRx-001 is more highly targeted than, for example, the kinase inhibitors, which carry a label of 'precision medicine' and are referred to as 'targeted', but because binding can occur in all tissues of the body, can result in off-target (nontumor specific) toxicities that affect virtually every organ system in the body [34]. The ironic legacy of the molecularly targeted agents is that they are no less toxic or more 'precise' than the standard chemotherapy they were designed to replace, and while targeted therapies with broad activity, such as multikinase inhibitors, possess both activity and toxicity in equal measure, highly selective kinase inhibitors often have activity tuned out.…”
Section: Discussionmentioning
confidence: 99%
“…The CT findings range from ground-glass opacity with or without septal thickening to multifocal consolidations with traction bronchiectasis. Both a recently published meta-analysis (Shi et al 2014 ) and a review (Dy and Adjei 2013 ) reported an incidence of <1 % for pulmonary complications caused by erlotinib. The risk for drug-induced interstitial lung disease is higher in smokers and in patients with preexisting lung disease (Fig.…”
Section: Erlotinibmentioning
confidence: 99%
“…Chemotherapy works by taking advantage of the increased sensitivity to treatment of rapidly dividing cells; accordingly, it affects not only cancer cells but also normal actively dividing cells, including cells of the bone marrow, the digestive tract and hair follicles [5]. This lack of specificity explains some of the common side effects such as myelosuppression, mucositis and alopecia [6][7][8]. In addition to its low specificity, chemotherapy is also limited as a treatment method due to development of drug resistance by cancer cells.…”
Section: Introductionmentioning
confidence: 99%